Cost-effectiveness of mirtazapine for agitated behaviors in dementia: findings from a randomized controlled trial. (19th July 2022) - Henderson, Catherine; Knapp, Martin; Stirling, Susan; Shepstone, Lee; High, Juliet; Ballard, Clive; Bentham, Peter; Burns, Alistair; Farina, Nicolas; Fox, Chris; Fountain, Julia; Francis, Paul; et al.
ABSTRACT: Objectives: To examine the costs and cost-effectiveness of mirtazapine compared to placebo over 12-week follow-up. Design: Economic evaluation in a double-blind randomized controlled trial of mirtazapine vs. placebo. Setting: Community settings and care homes in 26 UK centers. Participants: People with probable or possible Alzheimer's disease and agitation. Measurements: Primary outcome included incremental cost of participants' health and social care per 6-point difference in CMAI score at 12 weeks. Secondary cost-utility analyses examined participants' and unpaid carers' gain in quality-adjusted life years (derived from EQ-5D-5L, DEMQOL-Proxy-U, and DEMQOL-U) from the health and social care and societal perspectives. Results: One hundred and two participants were allocated to each group; 81 mirtazapine and 90 placebo participants completed a 12-week assessment (87 and 95, respectively, completed a 6-week assessment). Mirtazapine and placebo groups did not differ on mean CMAI scores or health and social care costs over the study period, before or after adjustment for center and living arrangement (independent living/care home). On the primary outcome, neither mirtazapine nor placebo could be considered a cost-effective strategy with a high level of confidence. Groups did not differ in terms of participant self- or proxy-rated or carer self-rated quality of life scores, health and social care or societal costs, before or after adjustment. Conclusions: On cost-effectiveness grounds, the use of mirtazapine cannot be recommended for agitated behaviors in people living with dementia. Effective and cost-effective medications for agitation in dementia remain to be identified in cases where non-pharmacological strategies for managing agitation have been unsuccessful.